2017
DOI: 10.4258/hir.2017.23.1.60
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the DeLone and McLean Information Systems Success Model

Abstract: ObjectivesThis study is an adaptation of the widely used DeLone and McLean information system success model in the context of hospital information systems in a developing country.MethodsA survey research design was adopted in the study. A structured questionnaire was used to collect data from 442 health information management personnel in five Nigerian teaching hospitals. A structural equation modeling technique was used to validate the model's constructs.ResultsIt was revealed that system quality significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
131
4
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(171 citation statements)
references
References 20 publications
21
131
4
15
Order By: Relevance
“…The above result supports Ojo's (2017) analysis, which also shows an insignificant association between technology use and user satisfaction. Furthermore, technology use and user satisfaction were postulated to influence technology benefits, confirming the findings of earlier research (Ojo, 2017;Ramirez-Correa et al, 2017) and corresponding to the original assumption of the D&M ISS model (DeLone & McLean, 1992). Table 7 summarizes the similarities and differences between the current study findings and some of the previous literature.…”
Section: Discussionsupporting
confidence: 81%
“…The above result supports Ojo's (2017) analysis, which also shows an insignificant association between technology use and user satisfaction. Furthermore, technology use and user satisfaction were postulated to influence technology benefits, confirming the findings of earlier research (Ojo, 2017;Ramirez-Correa et al, 2017) and corresponding to the original assumption of the D&M ISS model (DeLone & McLean, 1992). Table 7 summarizes the similarities and differences between the current study findings and some of the previous literature.…”
Section: Discussionsupporting
confidence: 81%
“…Rai and others (Rai et al, 2002) tested these models and found that the models are relatively acceptable/valid despite other researchers commenting that the models do not necessarily have an impact (Lee 2012). The model has even been tested recently (Tam and Oliveira 2017, Van Cauter et al 2017, Ojo, 2017.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The better the system characteristics, the more users utilize it and the more satisfied they will be. (DeLone and McLean, 2003, Ojo, 2017, and Rizal et al, 2018. At the moment, the system website utilizes WEB 2.0 that emphasize user centered design.…”
Section: Impact Of System Characteristics On Membership Valuementioning
confidence: 99%